1998
DOI: 10.1161/01.str.29.1.190
|View full text |Cite
|
Sign up to set email alerts
|

A Glycine Site Antagonist, ZD9379, Reduces Number of Spreading Depressions and Infarct Size in Rats With Permanent Middle Cerebral Artery Occlusion

Abstract: Background and Purpose-Spreading depressions (SDs) occur in experimental focal ischemia and contribute to lesion evolution. N-Methyl-D-aspartate (NMDA) antagonists inhibit SDs and reduce infarct size. The glycine site on the NMDA receptor complex offers a therapeutic target for acute focal ischemia, potentially devoid of many side effects associated with competitive and noncompetitive NMDA antagonists. We evaluated the effect of the glycine antagonist ZD9379 on SDs and brain infarction. Methods-Male Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Previous studies have shown that NMDA receptor antagonists depress the activation of spreading depression in vivo (Marrannes et al, 1988;Gill et al, 1992;McLachlan, 1992;Nellgard and Wieloch, 1992;Martin et al, 1994;Willette et al, 1994;Obrenovitch and Z ilkha, 1996;Tatlisumak et al, 1998). Our results point to a pivotal role for NMDA receptor activation in the initial onset of SD.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have shown that NMDA receptor antagonists depress the activation of spreading depression in vivo (Marrannes et al, 1988;Gill et al, 1992;McLachlan, 1992;Nellgard and Wieloch, 1992;Martin et al, 1994;Willette et al, 1994;Obrenovitch and Z ilkha, 1996;Tatlisumak et al, 1998). Our results point to a pivotal role for NMDA receptor activation in the initial onset of SD.…”
Section: Discussionsupporting
confidence: 67%
“…1 A). Previous reports (Marrannes et al, 1988;Gill et al, 1992;McLachlan, 1992;Nellgard and Wieloch, 1992;Martin et al, 1994;Willette et al, 1994;Obrenovitch and Zilkha, 1996;Tatlisumak et al, 1998) have demonstrated that spreading depression in vivo is delayed or inhibited by glutamate receptor antagonists. In hippocampal brain slices, application of the noncompetitive NMDA receptor antagonist MK-801 (50 M) inhibited the onset of spreading depression (Fig.…”
Section: Glutamate Is Involved In the Initial Phase Of Spreading Deprmentioning
confidence: 94%
“…This relationship may be causal, because eliciting SpD remote from the infarct region [i.e., by potassium application (Busch et al, 1996;Takano et al, 1996) or electrical stimulation (Back et al, 1996)] results in larger infarct volumes. Accordingly, administration of drugs (Gill et al, 1992;Iijima et al, 1992;Mies et al, 1993Mies et al, , 1994Rawanduzy et al, 1997;Tatlisumak et al, 2000) or physiologic treatments (Chen et al, 1993) that decrease the frequency of SpD associated with ischemic injury is also neuroprotective.…”
Section: Introductionmentioning
confidence: 99%
“…Как свидетельствуют немногочисленные публикации по данной проблеме, практически единственным малоинвазивным методом исследования поляризационных процессов является регистрация УПП [13,17,18]. Альтерирующее действие деполяризации связывается с нарушением ионного гомеостаза, резким увеличением метаболической нагрузки при ишемии, что приводит к несоответствию между потребностью в энергетических субстратах и их поступлением в ткань [12,22]. Объем ишемического повреждения преимущественно связан с общим временем ишемической деполяризации [11].…”
Section: Discussionunclassified